Workshop on Biofuels and food security interactions: Report of the scientific committee - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Over the dates 20-22 Nov 2014, an international workshop on the interactions of biofuels and food security was held at IFPRI headquarters, in Washington DC. The workshop brought together 61 scholars and experts representing over 30 different organizations interested in biofuel and food security across six continents. The Workshop agenda and full list of participants are included as appendices to this report. The purpose of the workshop was to explore current and future interactions between biofuels and food security, and elaborate learnings from analysis and field experience relevant for project developers, researchers and policy-makers. The workshop was organized around six discussion topics and was designed to encourage discussion among participants. The key aim was to identify where consensus lies regarding key barriers, gaps and opportunities related to (a) the assessment of biofuel-food security interactions and (b) recommendations for future research and implementation.